Validity of child psychiatric screening methods. - Kresanov K; Tuominen J; Piha J; Almqvist F (European Child & Adolescent Psychiatry, 1998)
Abstract The Parent Questionnaire (scale A2), the Teacher Questionnaire (scale B2) by Rutter, and the Children's Depression Inventory (CD1) were validated using ROCanalysis. The material was collected from an epidemiological study of a normal population of 5664 8-9 year-old children. The screening results were compared with the corresponding parent, teacher, and child (DISC) interviews. In addition to this traditional way of validating the combined interview, results from all three interviews were also used. We found that the Teacher Questionnaire scale B2 was the most valid, and had the best overall power to discriminate psychiatric disturbances. The Teacher Questionnaire (scale B2) may be recommended when screening child psychiatric disturbances. The Parent Questionnaire (scale A2) was also found to be a valid instrument. Our results do not support the use of CDI as a sole screening instrument of psychiatric disturbances in children.